Analisis Penggunaan Antibiotik dengan Metode ATC/DDD dan DU90% di Puskesmas Banjarbaru Selatan Tahun 2023-2024 - Sari, Okta Muthia; Intannia, Difa; Lingga, Herningtyas Nautika; Sandi, Dita Ayulia Dwi; Setiawan, Deni; Andini, Rizka Syawal; Dania, Sri Rahmah (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
Antibiotic resistance is an escalating global health concern, with Indonesia increasingly reporting resistance across various bacterial species. This trend contributes to rising morbidity and mortality and influences patterns of antibiotic use, highlighting the need for systematic monitoring. The Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) methodology is a widely accepted standard for evaluating antibiotic consumption and serves as a key indicator of antimicrobial stewardship effectiveness. This study aimed to: (i) identify the most consumed antibiotics based on DDD/1000 outpatient visits, (ii) compare consumption between 2023 and 2024, and (iii) determine the DU90% segment of antibiotic use at Banjarbaru Selatan Health Center. A quantitative, descriptive, cross-sectional design was conducted from January to May 2025, involving adult outpatients prescribed antibiotics during 2023–2024. Data analysis included DDD/1000 outpatient visit calculations and year-to-year comparisons using the Wilcoxon test. Amoxicillin consistently showed the highest consumption, with 272.94 DDD/1000 outpatient visits in 2023 and 274.26 in 2024. Statistical analysis revealed no significant difference in overall antibiotic use between the two years (p = 0.063). DU90% analysis identified Amoxicillin as the dominant antibiotic in 2023, while Amoxicillin and Cefadroxil led in 2024. Antibiotic consumption at Banjarbaru Selatan Health Center remained stable over the two years, with Amoxicillin as the predominant agent. These findings underscore the importance of routine monitoring using ATC/DDD and DU90% methodologies to inform targeted interventions and enhance antimicrobial resistance control strategies.